Characterization of two novel HIV-1 second-generation recombinants (CRF01_AE/CRF07_BC) identified in Hebei Province, China - Yang, Xuegang; Zhao, Na; Su, Miaomiao; Meng, Juan; Du, Jian; An, Weina; Shi, Haoxi; Fan, Weiguang (Frontiers in Microbiology, 2023)
Introduction The unique recombinant forms (URFs) of HIV-1 consist of a mixture of subtypes, and each URF has a unique breakpoint. In this study, we identified the near fulllength genome (NFLG) sequences of two novel HIV-1 URFs (Sample ID: BDD034A and BDL060) isolated during HIV-1 molecular surveillance in 2022 in Baoding city, Hebei Province, China. Methods The two sequences were aligned with subtype reference sequences and CRFs from China using MAFFT v7.0, and the alignments were adjusted manually using BioEdit (v7.2.5.0). Phylogenetic and subregion trees were constructed using MEGA11 with the neighbor-joining (N-J) method. Recombination breakpoints were identified by SimPlot (v3.5.1) based on Bootscan analyses. Results Recombinant breakpoint analysis revealed that the NFLGs of BDD034A and BDL060 were composed of CRF01_AE and CRF07_BC, containing seven segments, respectively. For BDD034A, three CRF01_AE fragments were inserted into the CRF07_BC main framework, whereas for BDL060, three CRF07_BC fragments were inserted into the CRF01_AE main framework. Discussion The emergence of the CRF01_AE/CRF07_BC recombinant strains indicates that HIV-1 co-infection is common. The increasing genetic complexity of the HIV-1 epidemic in China warrants continued investigation.